REGIONAL DISPARITIES AND OPPORTUNITIES FOR AGRICULTURAL GROWTH: A SPATIAL ANALYSIS ABOUT JHUNJHUNU DISTRICT OF RAJASTHAN, INDIA - Khinchi, Shyam S.; Kumar, Amit (International Journal of Research -GRANTHAALAYAH, 2025)
Analyzing agricultural progress and opportunities in Rajasthan, India’s Jhunjhunu district is the primary goal of the present research. Agricultural planners, social workers, and officials carrying out development projects can learn from the study. The intention is to make recommendations in order to properly construct a plan for agricultural development and opportunities in the area under consideration. The current study’s research aims have been maintained in light of these. In India as a whole, it is currently getting harder to keep up traditional core business in a timely and balanced manner. In actuality, agriculture is a business that is affected by the environment. However, the Jhunjhunu district in Rajasthan, India, has seen more pollution and impacts from human activity than any other business. The regional disparity in agricultural growth has been evaluated within the framework of Jhunjhunu district, taking into account geographical factors. This study emphasizes the significance of sustainable land management practices in the Jhunjhunu area of Rajasthan, India, in order to address regional disparities and investigate prospects for agricultural development.